Testing of market price direction dependence on US stock market - Stádník, Bohumil (Business, Management and Economics Engineering, 2012)
The correct model of a liquid financial market is very important for all market activities including for example a stock or bond portfolio management or an asset valuation. Dynamic Financial Market Model is a comprehensive model with a detailed interpretation. The model considers also feedback processes which cause price development direction dependence on the previous development. This is why it is also able to explain departures from normality as leptokurtic deformations with fat tails and sharpness, extreme values or skewness in the returns’ probability distributions. These departures are commonly explained using a wide range of models with volatility dependence. The question is then arising, whether the volatility or direction dependence is more in accordance with reality. Price Inertia Feedback is one of the most important and has a direct impact on probability distribution and also on a price forecasting. Empirical measurement of this feedback is the core of the paper.